Effects of chronic exposure to triclosan on reproductive and thyroid endpoints in the adult Wistar female rat. Issue 4 (16th February 2017) - Louis, Gwendolyn W.; Hallinger, Daniel R.; Braxton, M. Janay; Kamel, Alaa; Stoker, Tammy E.
ABSTRACT: Triclosan (TCS), an antibacterial, has been shown to be an endocrine disruptor in the rat. Previously, subchronic TCS treatment to female rats was found to advance puberty and potentiate the effect of ethinyl estradiol (EE) on uterine growth when EE and TCS were co-administered prior to weaning. In the pubertal study, a decrease in serum thyroxine (T4 ) concentrations with no significant change in serum thyroid-stimulating hormone (TSH) was also observed. The purpose of the present study was to further characterize the influence of TCS on the reproductive and thyroid axes of the female rat using a chronic exposure regimen. Female Wistar rats were exposed by oral gavage to vehicle control, EE (1 μg/kg), or TCS (2.35, 4.69, 9.375 or 37.5 mg/kg) for 8 months and estrous cyclicity monitored. Although a divergent pattern of reproductive senescence appeared to emerge from 5 to 11 months of age between controls and EE-treated females, no significant difference in cyclicity was noted between TCS-treated and control females. A higher % control females displayed persistent diestrus (PD) by the end of the study, whereas animals administered with positive control (EE) were predominately persistent estrus (PE). Thyroxine concentration was significantly decreased in TCS-administered 9.375 and 37.5 mg/kg groups, with no marked effects on TSH levels, thyroid tissue weight, or histology. Results demonstrate that a long-term exposure to TCS did not significantly alter estrous cyclicity or timing of reproductive senescence in females but suppressed T4 levels at a lower dose than previously observed.